Perfil do idoso do bairro Camobi, Santa Maria/RS: qualidade de vida e cidadania - Lopes, Carmen Lucia Colvero (2013)
The progressive increase in the number of elderly in recent decades as a result of declining fertility and mortality rates and the consequent increase in life expectancy, made to develop interest in the study of aging. The literature highlighted the scientific and social relevance of investigating the conditions that affect the well -being and the factors associated with quality of life of elderly people in order to create alternative intervention and propose actions and policies, seeking to meet the demands of the population aging. Thus, this study aims to profile the Elderly Camobi Subdivision, located in the municipality of Santa Maria, RS, Brazil. The research was done with quantitative and qualitative approaches and data collection was conducted through questionnaires. The analysis of the findings shows that older respondents value their independence and autonomy in the conduct of its activities. Attribute a healthy and appropriate behavior in relation to health care, and excel leisure activities, participation in groups and good relationships as essential for personal satisfaction. Indicate that the social activities and leisure are extremely important to have a good quality of life. Older people positively evaluate their quality of life. The variables that contributed most to this positive assessment were personal relationships, the support they receive from family and friends, physical environment inhabited by the health care they receive and the means of transport they use. Quality of life was better evaluated. The study also helped to know the reality of the elderly and thereby provide subsidy to the competent organs create new policies in relation to aging and providing better quality of life.